Nutritional care of preterm infants : scientific basis and practical guidelines - Alshaikh, Belal; Arslanoglu, Sertac; Barbanti, Claudio; Belfort, Mandy B.; Bellagamba, Maria Paola; Koletzko, Berthold 1954- (Basel : Karger, 2021)
Improved conditions of care for premature infants have led to markedly increased survival rates over the last few decades, particularly in very low and extremely low birth weight infants. Nutritional measures play a central role in the long-term outcome, health, and quality of life of these premature infants. In this updated and extended edition, leading experts from all over the world present the most recent evidence and critical analyses of nutrient requirements and the practice of nutritional care (with the focus on very low birth weight infants) to provide guidance for clinical application. The chapters of this publication show how growth and development can be nutritionally supported, which nutrients and non-nutrients can be supplied, and how nutritional care can get implemented. Approaches to nutritional care in various disease conditions are also addressed. The compilation of current information and recommendations should support the daily work of health care professionals such as neonatologists, paediatricians, other physicians involved in the care of preterm infants, nurses, nutritionists/dieticians, and others. The current book is also of interest for researchers who wish to keep up to date in this moving field.
La función de los autores fue determinada por el catalogador
Keywords: NIÑOS PREMATUROS -- NUTRICIÓN; BAJO PESO AL NACER; NIÑOS PREMATUROS -- CUIDADO E HIGIENE